Life history of the individuals buried in the St. Benedict Cemetery (Prague, 15th–18th Centuries): Insights from 14C dating and stable isotope (δ13C, δ15N, δ18O) analysis. Issue 2 (16th April 2013) - Salesse, Kevin; Dufour, Élise; Castex, Dominique; Velemínský, Petr; Santos, Frédéric; Kuchařová, Hedvika; Jun, Libor; Brůžek, Jaroslav
ABSTRACT Funerary practices and bioarchaeological (sex and age) data suggest that a mortality crisis linked to an epidemic episode occurred during the fifth phase of the St. Benedict cemetery in Prague (Czech Republic). To identify this mass mortality episode, we reconstructed individual life histories (dietary and mobility factors), assessed the population's biological homogeneity, and proposed a new chronology through stable isotope analysis (δ13C, δ18O and δ15N) and direct radiocarbon dating. Stable isotope analysis was conducted on the bone and tooth enamel (collagen and carbonate) of 19 individuals from three multiple graves (MG) and 12 individuals from individual graves (IG). The δ15N values of collagen and the difference between the δ13C values of collagen and bone carbonate could indicate that the IG individuals had a richer protein diet than the MG individuals or different food resources. The human bone and enamel carbonate and δ18O values suggest that the majority of individuals from MG and all individuals from IG spent most of their lives outside of the Bohemian region. Variations in δ18O values also indicate that all individuals experienced residential mobility during their lives. The stable isotope results, biological (age and sex) data and eight 14C dates clearly differentiate the MG and IG groups. The present work provides evidence for the reuse of the St. Benedict cemetery to bury soldiers despite the funeral protest ban (1635 AD). The Siege of Prague (1742 AD) by French‐Bavarian‐Saxon armies is identified as the cause of the St. Benedict mass mortality event. Am J Phys Anthropol 151:202–214, 2013. © 2013 Wiley Periodicals, Inc.